Rearing Practices Performed by Mothers and Fathers to Adolescents from a Rural Area in the State of Mexico: An Exploratory Study - Oudhof Van Barneveld, Hans (Consorcio de Universidades Mexicanas A.C., 2013)
An exploratory study was carried out with the purpose of identifying the rearing practices performed by mothers and fathers from a rural area in the State of Mexico. A nonprobabilistic quota sample of 30 mothers and fathers with adolescent children was employed. A questionnaire, designed for determining the basic aspects of parental rearing, was administered. The results indicate that a traditionalist labor division by gender prevails; mothers have the main responsibility for taking care of their offspring. The primordial activities carried out for children’s education are promoting their performance at school, communication, transmitting values, giving advice and support. A great variety of structures which parents attribute to themselves in their educating role was obtained, such as comprehensive, demanding, responsible and loving. The most frequently reported strategies for children’s disobedience are scolding, talking with them, non-physical punishment and trying to correct their behavior. It is concluded that the rearing practices reported by the participants do not match the stereotyped image of family socialization in rural areas.